Masalah-Masalah dalam Paradigma Pembelajaran Sains Modern - Zahid Zufar At Thaariq; Reno Nurdiyanto; Devi mariya Sulfa (Jounal Nyanadassana, 2023)
Modern science learning paradigms emphasize inquiry-based and experiential learning, replacing traditional approaches. Constructivist approaches become the theoretical foundation, recognizing the importance of students' active involvement in the learning process. Metaphors of acquisition and participation are proposed as the basis for understanding science learning. The research method uses narrative techniques to synthesize information from multiple sources, providing a comprehensive overview of problems and solutions in the contemporary science learning paradigm. The author highlights a number of issues that need to be addressed. Key challenges include a lack of hands-on experimentation, an overemphasis on rote learning, a lack of inclusivity, and suboptimal integration of technology. While technology integration has the potential to enrich the student experience, there are still shortcomings in its implementation. By highlighting these issues, the authors promote the importance of hands-on experiences, concept-based assessments, inclusive curricula, and effective technology integration in improving science education. Recommendations include a collaborative approach among educators, policymakers, and stakeholders to address these issues and create a better future for science education. The conclusions emphasize the need to implement these solutions in the classroom and in education policy. By improving the student experience, supporting student-centered learning, and addressing the challenges of technology integration, science education can evolve to meet the demands of today's society and science.